The Ape That Lived to Tell the Tale. The Evolution of the Art of Storytelling and Its Relationship to Mental Time Travel and Theory of Mind - Garcia-Pelegrin, Elias; Wilkins, Clive; Clayton, Nicola S. (Frontiers in Psychology, 2021)
Engaging in the art of creating and telling stories is a defining behaviour of humankind. Humans have been sharing stories with each other, with and without words, since the dawn of recorded history, but the cognitive foundations of the behaviour can be traced deeper into our past. The emergence of stories can be strongly linked to Mental Time Travel and plays a key role in our ability to communicate past, present and future scenarios with other individuals, within and beyond our lifetimes. Stories are products engraved within the concept of time, constructed to elucidate the past experiences of the self, but designed with the future in mind, thus imparting lessons of such experiences to the receiver. By being privy to the experiences of others, humans can imagine themselves in a similar position to the protagonist of the story, thus mentally learning from an experience they might have never encountered other than in the mind’s eye. Evolutionary Psychology investigates how the engagement in art by our ancestors granted them an advantage in surviving and reproducing and questions whether art is an adaptation of the human mind. However, little attention has been placed on the cognitive abilities that might have been imperative for the development of art. Here, we examine the relationship between storytelling, Mental time Travel and Theory of Mind. We suggest that Mental Time Travel played a key role in the development of storytelling because through stories, humans can fundamentally transcend their present condition, by being able to imagine different times, separate realities, and place themselves and others anywhere within the time space continuum. We argue that the development of a Theory of Mind also sparked storytelling practices in humans as a method of diffusing the past experiences of the self to others whilst enabling the receiver to dissociate between the past experiences of others and their own, and to understand them as lessons for a possible future. We propose that when artistic behaviours use storytelling as a method of communication, they ought to be considered separate from other forms of art whose appreciation capitalise on our aesthetic preferences.